Methods to collect and interpret external training load using microtechnology incorporating GPS in professional football: a systematic review - Rago, V.; Brito, J.; Figueiredo, F.; Costa, J.; Barreira, D.; Krustrup, P.; Rebelo, A. (Research in Sports Medicine, 2020)
The aim of this article was to systematically review the methods adopted to collect and interpret external training load (ETL) using microtechnology incorporating global positioning system (GPS). The main deficiencies identified concerned the non-collection of match ETL, and the non-consideration of potential confounders (e.g. playing position, fitness level, starting status or session content). Also, complementary training (individual/reconditioning) and pre-match warm-up were rarely quantified. To provide a full picture of the training demands, ETL was commonly complemented by internal training load monitoring with the rating of perceived exertion predominantly adopted instead of heart rate recordings. Continuous data collection and interpretation of ETL data in professional football vary widely between observational studies, possibly reflecting the actual procedures adopted in practical settings. Evidence about continuous ETL monitoring in female players, and female as well as male goalkeepers is lacking.